CADRE EDUCATION MODEL IN PARTY CADRE AGENCIES TO REALIZE A RELIGIOUS NATIONALIST CULTURE - Masrur Anhar; Rosyada, Dede; Luthfi, Atabik (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Cadre education is seen as a fundamental instrument in shaping the quality of the party's human resources who not only have ideological and leadership capacity, but also have national character and are based on religious values. Purpose: This study aims to examine and formulate a model of cadre education at the Party Cadre Development Agency conducted by the Crescent Star Party as a strategic effort to realize a religious nationalist culture within the political organization. Method: This study uses a qualitative approach with a descriptive-analytical study method, through data collection techniques in the form of in-depth interviews, observations, and documentation studies of cadre education activities organized by the Party Cadre Development Agency. Result: The results of the study indicate that an effective cadre education model in building a religious nationalist culture is implemented through the integration of nationalist and religiosity values ​​into the cadre development curriculum, participatory learning methods, and the habituation of cadre attitudes and behaviors in organizational practices.